A field study of the opioid market: Authenticity and price from pharmacy to street - Roger Bate (American Enterprise Institute (AEI), 2018)
With the assistance of pain patients, the opioids oxycodone and hydrocodone were assessed from licit and illicit sources in Philadelphia and surrounding counties. Sources included brick-and-mortar pharmacies, web pharmacies operating illegally by selling products without prescriptions, other internet sources such as social media fora, and private dealers. Pricing information was collected, and products were authenticated using Raman spectroscopy. All the legally obtained products were cheap and authentic, the web pharmacy and other internet products procured without prescription were more expensive, and a few were not authentic. Privately procured or assessed products were far more expensive, and over 15 percent were not authentic. If replicated in larger and better stratified studies, this result could indicate some problems for individual health and current policy if pain patients are driven from legal to illegal markets.
Keywords: 330